Right ventricular function in grown-up patients after correction of congenital right heart disease - Lemmer, Julia; Euler, Grit; Rentzsch, Axel; Böttler, Petra; Kühne, Titus; Dubowy, Karl-Otto; Peters, Brigitte; Lemmer, Björn; Hager, Alfred; Stiller, Brigitte (Clinical research in cardiology, 2011)
We investigated whether a correlation exists between biomarkers of the neurohumoral system and clinical markers in grown-up patients with congenital heart disease (GUCH) and right ventricular function.